Mental health care needs and use of services in Mexican population with serious mental disorders - Lina Díaz-Castro; Héctor Cabello-Rangel; María Elena Medina-Mora; Shoshana Berenzon-Gorn; Rebeca Robles-García; Eduardo Ángel Madrigal-de León (Instituto Nacional de Salud Pública, 2019)
Objective. To analyze the mental health care needs of the serious mental disorders (SMD) and factors associated with the use of services in Mexico. Materials and methods. A cross-sectional analytical study was conducted in two phases, the first with a national database of available services and its utilization; the second, a sample of medical records of a psychiatric hospital. Results. Schizophrenia is the most prevalent MDS; more than 50% of those hospitalized were male, with an average age of 37 years. The use of services was associated with age (β=1.062, p=.000), family income (β=1.000, p=.000) and no laboral occupation (β=3.407, p=.000). The population with schizophrenia is four times more likely to require to be exempt from payment (β=4.158, p=.000). Conclusions. The population with SMD as schizophrenia is more vulnerable due to the associated functional and social disability and it requires specific heath interventions and a financial protection policy adapted to their mental health care needs.